The terrible two get worse ebook - Barnett, Mac (Terrible Two, 2016)
On their own, pranksters Miles and Niles were pretty devious. Now that they've formed a pranking duo, they're terrible! But their powers will be tested when their favorite nemesis, Principal Barkin, is replaced by his stern and cunning father, Former Principal Barkin. Now Miles and Niles will do just about anything to get their old antagonist back—including pranking alongside him. Authors and friends Mac Barnett and Jory John "are in perfect comic harmony" ( Publishers Weekly ) in this series that celebrates inventiveness, friendship, and the power of teamwork—for good, or for terrible.